TRANSLATION PROBLEMS OF PHRASEOLOGICAL UNITS IN ENGLISH - To‘xtaqulova Oygul Xasan qizi (International Journal of Literature and Language Studies, 2026)
Phraseological units occupy a special place in the lexical and cultural system of every language. They are fixed or semi-fixed combinations of words whose meanings often cannot be fully understood from the meanings of their individual components. In English, phraseological units include idioms, proverbs, sayings, phrasal expressions, collocations, clichés and other stable word combinations. Their translation creates serious difficulties because they are closely connected with national mentality, cultural experience, historical memory, figurative thinking and communicative traditions. The present article investigates the major problems that appear in the translation of English phraseological units into another language, with particular attention to semantic, cultural, stylistic and pragmatic aspects. The study is based on descriptive, comparative and analytical methods. It examines the nature of phraseological meaning, the problem of equivalence, the role of context, and the translator’s choice between literal translation, phraseological equivalence, descriptive translation, substitution and omission. The results show that the main difficulties arise when an English phraseological unit has no direct equivalent in the target language, contains culture-specific imagery, includes historical or literary allusions, or carries an emotional and stylistic effect that is difficult to reproduce. The article concludes that successful translation of phraseological units requires not only linguistic knowledge but also cultural competence, contextual sensitivity and creative decision-making.